At high stocking rates, cattle do not functionally replace wild herbivores in shaping understory community composition. Issue 3 (15th February 2022) - Wells, Harry B. M.; Porensky, Lauren M.; Veblen, Kari E.; Riginos, Corinna; Stringer, Lindsay C.; Dougill, Andrew J.; Namoni, Mathew; Ekadeli, Jackson; Young, Truman P.
Abstract: Over a quarter of the world's land surface is grazed by cattle and other livestock, which are replacing wild herbivores, potentially impairing ecosystem structure, and functions. Previous research suggests that cattle at moderate stocking rates can functionally replace wild herbivores in shaping understory communities. However, it is uncertain whether this is also true under high stocking rates and the effects of wild herbivore on plant communities are moderate, enhanced, or simply additive to the effects of cattle at high stocking rates. To evaluate the influence of cattle stocking rates on the ability of cattle to functionally replace wild herbivores and test for interactive effects between cattle and wild herbivores in shaping understory vegetation, we assessed herbaceous vegetation in a long‐term exclosure experiment in a semi‐arid savanna in central Kenya that selectively excludes wild mesoherbivores (50–1000 kg) and megaherbivores (elephant and giraffe). We tested the effects of cattle stocking rate (zero/moderate/high) on herbaceous vegetation (diversity, composition, leafiness). We also tested how those effects depend on the presence of wild mesoherbivores and megaherbivores. We found that herbaceous community composition (primary ordination axis) was better explained by the presence/absence of herbivore types than by total herbivory, suggesting that herbivore identity is a more important determinant of community composition than total herbivory at high cattle stocking rates. The combination of wild mesoherbivores and cattle stocked at high rates led to increased bare ground and annual grass cover, reduced perennial grass cover and understory leafiness, and enhanced understory diversity. These shifts were weaker or absent when cattle were stocked at high stocking rates in the absence of wild mesoherbivores. Megaherbivores tempered the effects of cattle stocked at high rates on herbaceous community composition but amplified the effects of high cattle stocking rate on bare ground and understory diversity. Our results show that cattle at high stocking rates do not functionally replace wild herbivores in shaping savanna herbaceous communities contrary to previous findings at moderate stocking rates. In mixed‐use rangelands, interactions between cattle stocking rate and wild herbivore presence can lead to non‐additive vegetation responses with important implications for both wildlife conservation and livestock production.